2004
DOI: 10.1186/cc2926
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction We report a case of twin toddlers who both suffered near drowning but with different post-trauma treatment and course, and different neurological outcomes. Methods and results Two twin toddlers (a boy and girl, aged 2 years and 3 months) suffered hypothermic near drowning with protracted cardiac arrest and aspiration. The girl was treated with mild hypothermia for 72 hours and developed acute respiratory dysfunction syndrome and sepsis. She recovered without neurological deficit. The boy's treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…101 Our literature search yielded multiple case reports and retrospective reviews supporting neurologically intact survival in hypothermic patients, but several older studies showed no benefit. 102 114 There is no prospective study comparing TH to normothermia after ROSC in drowning patients. There might be benefit to discontinuing rewarming interventions after a hypothermic drowning patient has reached TH temperature range, but this has been insufficiently studied to support an evidence-based recommendation.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…101 Our literature search yielded multiple case reports and retrospective reviews supporting neurologically intact survival in hypothermic patients, but several older studies showed no benefit. 102 114 There is no prospective study comparing TH to normothermia after ROSC in drowning patients. There might be benefit to discontinuing rewarming interventions after a hypothermic drowning patient has reached TH temperature range, but this has been insufficiently studied to support an evidence-based recommendation.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…79 Our literature search yielded multiple case reports and retrospective reviews supporting neurologically intact survival in hypothermic patients, but several older studies showed no benefit. [80][81][82][83][84][85][86][87][88][89][90][91][92] There are no prospective studies comparing TH with normothermia after ROSC in drowning patients. There may be benefit to discontinuing rewarming interventions after a hypothermic drowning patient has reached TH temperature range, but this has been insufficiently studied to support an evidence-based recommendation.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…2 LOE 3 studies showing neutral effects [85, 296], 1 LOE 4 report indicating benefit [297], 1 LOE 4 report indicating a neutral effect [298], and 7 LOE 4 studies for which the effect was not specified [184, 266, 299-303]. These studies were all in drowning.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%